Directions of Resource Potential Development of Tiara LLC ("Journal "U". Economy. Management. Finance.", 2021)
The essence of the concept of the resource potential of the enterprise is considered, the analysis of the financial indicators of a commercial firm is made. The ways of development of the company are studied on the basis of the revision of the state of the company. Explore opportunities, set priorities and focus the company's work in connection with the planned strategy. The support of economic research helps to make a choice of alternative solutions among the many options for assessing the expected benefits.
Keywords: resource potential; production potential; economic indicators; industrial enterprise